Identification and Characterization of an Irreversible Inhibitor of CDK2. Issue 9 (17th September 2015) - Anscombe, Elizabeth; Meschini, Elisa; Mora-Vidal, Regina; Martin, Mathew P.; Staunton, David; Geitmann, Matthis; Danielson, U. Helena; Stanley, Will A.; Wang, Lan Z.; Reuillon, Tristan; Golding, Bernard T.; Cano, Celine; et al.
Summary: Irreversible inhibitors that modify cysteine or lysine residues within a protein kinase ATP binding site offer, through their distinctive mode of action, an alternative to ATP-competitive agents. 4-((6-(Cyclohexylmethoxy)-9 H -purin-2-yl)amino)benzenesulfonamide (NU6102) is a potent and selective ATP-competitive inhibitor of CDK2 in which the sulfonamide moiety is positioned close to a pair of lysine residues. Guided by the CDK2/NU6102 structure, we designed 6-(cyclohexylmethoxy)- N -(4-(vinylsulfonyl)phenyl)-9 H -purin-2-amine (NU6300), which binds covalently to CDK2 as shown by a co-complex crystal structure. Acute incubation with NU6300 produced a durable inhibition of Rb phosphorylation in SKUT-1B cells, consistent with it acting as an irreversible CDK2 inhibitor. NU6300 is the first covalent CDK2 inhibitor to be described, and illustrates the potential of vinyl sulfones for the design of more potent and selective compounds. Graphical Abstract: Highlights: NU6300 is the first example of a covalent CDK2 inhibitor A CDK2/cyclin A/NU6300 co-crystal structure reveals the inhibitor binding mode NU6300 is active in cells Abstract : Irreversible inhibitors have a distinctive mode of action and offer an alternative route to competitive ATP inhibitors to target protein kinases. Anscombe et al. describe NU6300, a covalent CDK2 inhibitor that illustrates the potential of using vinyl sulfones to mediate irreversible inhibition.